A magnesium-based composite hydrogen storage material, a preparation method and application thereof

CN118458691BActive Publication Date: 2026-10-16STATE PWR INVT CORP SHAANXI NEW ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311138289.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-05
Publication Date
2026-10-16
Estimated Expiration
2043-09-05

AI Technical Summary

Technical Problem

[0007]为了解决上述吸氢平台高吸放氢速率缓慢、制备工艺复杂问题,本发明提出一种新型镁蒸发纳米镁基复合储氢材料制备方法

Benefits of technology

[0018] Compared with existing technologies, this invention has at least the advantages of eliminating the need for magnesium powder, or directly using magnesium vapor in combination with the Pidgeon process for industrial magnesium production, thus reducing processing costs and manufacturing cycles, and lowering the cost of magnesium hydride raw materials by more than 60%. Compared with traditional methods for preparing nano-MgH2, it can effectively shorten the hydrogenation process and improve the degree of hydrogenation. Using magnesium vapor to blow CNT nanoparticles results in good mixing uniformity, which can effectively improve the kinetic properties of MgH2 and provide auxiliary diffusion channels for hydrogen. CNTs are porous materials that can absorb hydrogen themselves, have a stable structure and good reversibility. After hydrogen is introduced into magnesium vapor and fully reacted under the action of a trace amount of CNT catalyst, rapid cooling yields a novel MgH2-xCNTs composite material. Its main characteristics are that the nano-sized MgH2-xCNTs composite material helps to shorten the hydrogen diffusion distance, providing more diffusion channels for hydrogen and increasing the specific surface area. In addition, the formation energy barrier of hydrides in nanoparticles decreases with the increase of hydrogen atom solid solution, thereby reducing the apparent activation energy of hydrogen absorption/desorption reactions in magnesium-based hydrogen storage materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118458691B_ABST
    Figure CN118458691B_ABST
Patent Text Reader

Abstract

The application discloses a magnesium-based composite hydrogen storage material and a preparation method and application thereof, and has a chemical formula of MgH2-xCNTs, wherein CNTs are attached to the surface of MgH2 particles, and x=2-10 wt.%. Industrial magnesium blocks are heated to generate magnesium vapor under a hydrogen atmosphere; or industrial magnesium vapor is directly used, and the pressure is kept at 3-5 Mpa; indoor magnesium vapor and hydrogen are heated under a hydrogen atmosphere to form nanoscale gaseous MgH2; the gaseous MgH2 is driven by a hydrogen gas flow to pass through a partition plate to sweep CNTs on the partition plate; the escaped MgH2 vapor is rapidly cooled at a cooling rate of 20±5 ℃ / min, and MgH2-xCNTs composite powder is recovered at a cooling temperature of 20 ℃±5 ℃, which is beneficial to shortening the diffusion distance of hydrogen and providing more diffusion channels for hydrogen; the specific surface area is increased; and the formation energy barrier of hydride in the nanoscale particles is reduced with the increase of the solid solution amount of hydrogen atoms, so that the apparent activation energy of the hydrogen absorption / release reaction in the magnesium-based hydrogen storage material is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of hydrogen storage materials technology, specifically to a magnesium-based composite hydrogen storage material, its preparation method, and its application. Background Technology

[0002] Currently, the use of fossil fuels mainly brings two problems: energy resource scarcity and environmental pollution. Therefore, the development of new energy sources is urgent. Hydrogen energy has the advantages of high calorific value, zero pollution, and recyclability, making it a strong contender for future green energy. Currently, the best way to utilize hydrogen energy is through fuel cells. Reducing the manufacturing cost of fuel cells and developing safe, efficient, and lightweight fuel cell manufacturing technologies are key technical issues that urgently need to be addressed for vehicle-mounted fuel cell systems.

[0003] Magnesium hydride (MgH) 2)With a hydrogen content of 7.6 wt.% and abundant magnesium resources, MgH2 is one of the most attractive hydrogen storage materials. However, the limitations of MgH2 in practical applications mainly lie in the high bond energy of the Mg-H bond, resulting in a high hydrogen desorption temperature (approximately 603 K) and excessively high thermodynamic stability; the slow diffusion of hydrogen atoms in MgH2 leads to sluggish hydrogen absorption kinetics; and magnesium's extreme reactivity makes it highly susceptible to poisoning when exposed to air. To address these issues, current research largely focuses on improving thermodynamics through transition elements, alloys, and compound alloying, and on improving hydrogen absorption / desorption rates through the addition of catalysts. Traditional nano-sizing techniques such as reactive ball milling, gas-phase methods, nanoconfining methods, and liquid-phase reduction methods are used to prepare Mg nanoparticles and nanocomposites. Although some manufacturing methods can reduce the hydrogen desorption temperature through nano-sizing, the complex and energy-intensive processes hinder large-scale industrialization, preventing revolutionary progress in magnesium-based hydrogen storage materials. While some doping or alloying techniques can lower the hydrogen desorption temperature, high transition element content can cause magnesium-based hydrogen storage to lose its high-capacity advantage. Therefore, multi-element microalloying nano-sizing is the future development trend. However, this is always accompanied by a lower hydrogen storage capacity and a slower hydrogen absorption and desorption rate, because the oxidation of Mg and the addition of alloys or catalysts affect the matrix weight. The above improves the thermodynamics and kinetics of MgH2, but still cannot meet the requirements of the US Department of Energy for on-board solid hydrogen storage devices. Regarding the factors affecting the thermodynamic and kinetic performance of pure Mg in hydrogen storage, a lot of research has been done at home and abroad. The main conclusions are as follows: (1) Pure Mg powder can absorb hydrogen at hydrogen pressures higher than the hydrogen absorption plateau pressure under the conditions of 473-673K. However, as the hydrogen pressure increases, the maximum hydrogen absorption decreases. It can be seen that the number of surface nuclei during the MgH2 reaction is related to the hydrogen pressure. (2) The higher the hydrogen absorption temperature, the greater the hydrogen absorption and the faster the hydrogen absorption rate. Pure Mg powder has a slower hydrogen absorption rate at low temperatures. (3) The formation of MgO does not necessarily hinder the hydrogen absorption process of Mg. When MgO has a certain thickness and cracks, hydrogen can enter through the cracks and react with Mg. Therefore, it is advisable to passivate Mg powder appropriately. (4) Increasing the number of hydrogen absorption and desorption cycles does not significantly reduce the hydrogen storage capacity of pure Mg. Therefore, changing the reaction pathway of MgH2 to improve kinetics and increase the hydrogen absorption and desorption rate, promoting the breaking of Mg-H bonds to improve thermodynamics and reduce the hydrogen absorption and desorption temperature has become an urgent problem to be solved.

[0004] The existing technology still has the following problems: 1. Cost Issues: Processing magnesium blocks into powder would inevitably increase costs and add more steps, which is very uneconomical. Magnesium smelting, whether using electrolysis or thermal reduction, consumes a lot of energy. Magnesium is also a very reactive metal; magnesium powder has a large specific surface area, meaning it has a large contact area with air and is easily oxidized and deteriorated. Deteriorated magnesium will form a layer of MgO on its surface, making the reaction between Mg and H increasingly difficult, thus affecting the yield of magnesium hydride.

[0005] 2. Safety aspects: To prevent magnesium powder from floating into the air during processing, it is necessary to prevent it from exploding when the Mg content is 10-25 mg / L. Therefore, its safety is relatively poor.

[0006] 3. Pure magnesium powder has a limited ability to crack hydrogen and a long hydrogenation process. Summary of the Invention

[0007] To address the issues of slow hydrogen absorption / desorption rates and complex preparation processes in the aforementioned hydrogen absorption platforms, this invention proposes a novel method for preparing magnesium-based composite hydrogen storage materials using magnesium vaporization. Hydrogen gas is introduced into magnesium vapor, and after a complete reaction under the action of a trace amount of CNTs catalyst, rapid cooling yields a novel MgH2-xCNTs composite material. Its main characteristics are that the nano-sized MgH2-xCNTs composite material facilitates shorter hydrogen diffusion distances, providing more diffusion channels and increasing specific surface area. Furthermore, the formation energy barrier of hydrides in the nanoparticles decreases with increasing hydrogen atom solid solution content, thereby reducing the apparent activation energy of the hydrogen absorption / desorption reaction in the magnesium-based hydrogen storage material.

[0008] To achieve the above objectives, the technical solution adopted by this invention is: a magnesium-based composite hydrogen storage material with the chemical formula MgH2- x CNTs, CNTs attached to the surface of MgH2 particles, x=2 wt.%~10 wt.%; obtained by blowing nano-CNT powder with magnesium vapor and the resulting MgH2 under a hydrogen atmosphere, followed by rapid cooling. x CNT composite materials.

[0009] Furthermore, CNTs have an inner diameter of 3-5 nm, an outer diameter of 8-15 nm, and a length of 0.5-2 μm.

[0010] This invention also provides a method for preparing the magnesium-based composite hydrogen storage material, comprising the following steps: Magnesium vapor is generated by heating industrial magnesium blocks in a hydrogen atmosphere; or industrial magnesium vapor is used directly, with the pressure maintained at 3-5 MPa; in the hydrogen atmosphere, the magnesium vapor and hydrogen in the heating chamber fully form nano-sized gaseous MgH2, and the gaseous MgH2 is carried by the hydrogen flow to pass through the partition and blow away the CNTs on the partition. The escaped MgH2 vapor was rapidly cooled at a rate of 20±5℃ / min to recover MgH2- x CNTs composite powder, with a cooling temperature of 20℃±5℃.

[0011] Furthermore, magnesium vapor is generated by heating industrial magnesium blocks in a hydrogen atmosphere. Specifically, industrial magnesium blocks with a purity of not less than 99.98% are used. First, a vacuum is drawn, and then high-purity hydrogen is introduced under heating conditions at a hydrogen pressure of 3-5 MPa. The temperature is then heated to 900-1200℃ to generate magnesium vapor.

[0012] Furthermore, the industrial magnesium block is processed as follows: the surface oxide film is removed by polishing and grinding in a vacuum environment, the polished magnesium block is placed in a heating chamber, a vacuum is drawn, and then high-purity hydrogen is introduced at a hydrogen pressure of 1-3 MPa, and the process is repeated 2-3 times.

[0013] Furthermore, the purity of CNTs is >95%, with a mass range of 2wt.%-10wt.%, an inner diameter of 3-5nm, an outer diameter of 8-15nm, and a length of 0.5-2μm.

[0014] Furthermore, the partition in the heating chamber for placing CNTs materials has a one-way channel that allows only Mg / MgH2 vapor and hydrogen to pass through.

[0015] Furthermore, the temperature should be maintained at 700-850°C when collecting magnesium hydride powder.

[0016] Furthermore, magnesium hydride powder is formed by condensing magnesium hydride vapor using circulating cooling water, resulting in a rapid cooling rate.

[0017] Application of magnesium-based composite hydrogen storage materials obtained by the preparation method described in this invention in hydrogen storage devices.

[0018] Compared with existing technologies, this invention has at least the advantages of eliminating the need for magnesium powder, or directly using magnesium vapor in combination with the Pidgeon process for industrial magnesium production, thus reducing processing costs and manufacturing cycles, and lowering the cost of magnesium hydride raw materials by more than 60%. Compared with traditional methods for preparing nano-MgH2, it can effectively shorten the hydrogenation process and improve the degree of hydrogenation. Using magnesium vapor to blow CNT nanoparticles results in good mixing uniformity, which can effectively improve the kinetic properties of MgH2 and provide auxiliary diffusion channels for hydrogen. CNTs are porous materials that can absorb hydrogen themselves, have a stable structure and good reversibility. After hydrogen is introduced into magnesium vapor and fully reacted under the action of a trace amount of CNT catalyst, rapid cooling yields a novel MgH2-xCNTs composite material. Its main characteristics are that the nano-sized MgH2-xCNTs composite material helps to shorten the hydrogen diffusion distance, providing more diffusion channels for hydrogen and increasing the specific surface area. In addition, the formation energy barrier of hydrides in nanoparticles decreases with the increase of hydrogen atom solid solution, thereby reducing the apparent activation energy of hydrogen absorption / desorption reactions in magnesium-based hydrogen storage materials. Attached Figure Description Figure 1 A flowchart illustrating the preparation process of nano-sized magnesium-based composite hydrogen storage materials using magnesium vapor.

[0019] Figure 2 A flowchart illustrating the technical process for preparing nano-sized magnesium-based composite hydrogen storage materials using magnesium vapor.

[0020] Figure 3XRD diffraction pattern for preparing Mg-xCNTs magnesium-based composite hydrogen storage material using magnesium vapor.

[0021] Figure 4 SEM image of Mg-xCNTs magnesium-based composite hydrogen storage material prepared using magnesium vapor. Detailed Implementation

[0022] The present invention will be further described in detail below with reference to the embodiments.

[0023] refer to Figure 1 This invention provides a method for preparing a magnesium-based composite hydrogen storage material, comprising the following steps: heating an industrial magnesium block in a hydrogen atmosphere to generate magnesium vapor; or directly using industrial magnesium vapor while maintaining a set pressure; fully forming nanoscale gaseous MgH2 from the magnesium vapor and hydrogen in a heating chamber under a hydrogen atmosphere; the gaseous MgH2 passing through a partition and purging CNTs on the partition under the influence of a hydrogen gas flow; rapidly cooling the escaped MgH2 vapor at a cooling rate of 20±5℃ / min to recover MgH2- x CNTs composite powder; hydrogen gas and MgH2 vapor pass through a partition with a one-way channel. After cooling, CNTs adhere to MgH2 particles. CNTs are porous materials that can absorb hydrogen themselves. They have a stable structure and good reversibility. Using MgH2 vapor to blow CNT nanoparticles, the nano-sized MgH2-xCNTs composite material helps to shorten the diffusion distance of hydrogen, provides more diffusion channels for hydrogen, and increases the specific surface area.

[0024] Example 1 Pre-treated magnesium blocks with a purity ≥ 99.98% and CNTs were selected, with the mass of CNTs being 2 wt.% of the magnesium blocks. They were placed in the heating zone and on the partition plate of the heating chamber, respectively. A vacuum was drawn, and then high-purity hydrogen gas (purity > 99.99%) was introduced at a hydrogen pressure of 1-3 MPa, and the cycle was repeated 2-3 times. The temperature was heated to 900℃, and then high-purity hydrogen gas was introduced again to a pressure of 3 MPa for 1 hour. The mixture was then transferred to the collection chamber through a transmission pipeline at a brushing speed of 350W, and the temperature of the water cooling device outside the collection chamber was 20℃. Magnesium hydride powder was collected and subjected to PCT (Polyhydrogenation Therapy) to test hydrogen absorption and desorption kinetics at temperatures of 250℃, 300℃, and 350℃, with absorption and desorption times of 120 min and 60 min, respectively. The hydrogen pressure during absorption was 2-3 MPa, and the hydrogen absorption and desorption data were recorded. The temperature-dependent hydrogen desorption behavior was tested using DSC (Digital Subtraction Angiography) at heating rates of 5, 10, 15, and 20 K / min, with a heating temperature range of 50-500℃. Information such as the initial hydrogen desorption temperature and peak hydrogen desorption temperature of the magnesium-based composite hydrogen storage material was recorded, and the hydrogen desorption activation energy was calculated based on the peak hydrogen desorption temperature.

[0025] Example 2 Pre-treated magnesium blocks with a purity ≥ 99.98% and CNTs (CNTs weighing 6 wt.% of the magnesium blocks) were selected and placed in the heating zone and on the partition plate of the heating chamber, respectively. A vacuum was drawn, and then high-purity hydrogen gas (purity > 99.99%) was introduced at a pressure of 1-3 MPa, repeated 2-3 times. The mixture was then heated to 1000℃, and high-purity hydrogen gas was introduced again until the pressure reached 4 MPa. The magnesium hydride powder was subjected to a continuous 1.5-hour heat treatment at a pressure of 450 MPa. The powder was then transferred to the collection chamber via a pipeline at a rotation speed of 450 W, with an external water-cooling device at 20°C. The magnesium hydride powder was collected and subjected to PCT tests to assess hydrogen absorption and desorption kinetics at temperatures of 250°C, 300°C, and 350°C, with absorption and desorption times of 120 min and 60 min, respectively. The hydrogen pressure during absorption was 2-3 MPa. The temperature-dependent hydrogen desorption behavior was tested using DSC at heating rates of 5, 10, 15, and 20 K / min, with a heating temperature range of 50-500°C. The initial hydrogen desorption temperature and peak hydrogen desorption temperature of the magnesium-based composite hydrogen storage material were recorded, and the activation energy for hydrogen desorption was calculated based on the peak hydrogen desorption temperature.

[0026] Example 3 Pre-treated magnesium metal blocks with a purity ≥ 99.98% and CNTs (10 wt.% of the magnesium metal blocks) were selected and placed in the heating zone and on the partition plate of the heating chamber, respectively. A vacuum was drawn, and then high-purity hydrogen gas (purity > 99.99%) was introduced at a pressure of 1-3 MPa, cyclically repeated 2-3 times. The mixture was heated to 1100℃, and then high-purity hydrogen gas was introduced again until the pressure reached 5 MPa, maintained for 2 hours. The mixture was then transferred to the collection chamber via a transmission pipeline, with a brushing speed of 550 W and an external water-cooling device at 20℃. The magnesium hydride powder was collected using P... CT was used to test the hydrogen absorption and desorption kinetics at temperatures of 250℃, 300℃, and 350℃, with absorption and desorption times of 120 min and 60 min, respectively. The hydrogen pressure during absorption was 2-3 MPa. The hydrogen absorption and desorption data were recorded. DSC was used to test the temperature-dependent hydrogen desorption behavior at heating rates of 5, 10, 15, and 20 K / min, with a heating temperature range of 50-500℃. The initial hydrogen desorption temperature and peak hydrogen desorption temperature of the magnesium-based composite hydrogen storage material were recorded. The hydrogen desorption activation energy was calculated based on the peak hydrogen desorption temperature.

[0027] Regarding the characterization of hydrogen storage performance: For the variable-temperature hydrogen release test, the hydrogen absorption and release kinetics of the nano-sized magnesium-based composite hydrogen storage material produced by magnesium vapor production were tested using PCT at temperatures of 250℃, 300℃, and 350℃, with hydrogen absorption and release times of 120 min and 60 min, respectively. The hydrogen pressure during absorption was 2-3 MPa, and the hydrogen absorption and release data were recorded. For the variable-temperature hydrogen release behavior, DSC was used to test the heating rate of 5, 10, 15, and 20 K / min, with a heating temperature range of 50-500℃. Information such as the initial hydrogen release temperature and peak hydrogen release temperature of the magnesium-based composite hydrogen storage material was recorded, and the hydrogen release activation energy was calculated based on the peak hydrogen release temperature.

[0028] The magnesium-based composite hydrogen storage material prepared by the method of this invention can be used in hydrogen storage devices, specifically in vehicle-mounted solid hydrogen storage devices.

[0029] Regarding the PCT and DSC tests of the above three embodiments, this invention uses magnesium vapor to prepare nano-magnesium-based composite hydrogen storage materials. Using magnesium vapor can effectively reduce the grain size and shorten the transport path of hydrogen atoms. In addition, compared with magnesium particles, magnesium vapor can make the catalyst distribution more uniform and accelerate the cracking of hydrogen and the diffusion of hydrogen atoms. Figure 2 This is a flowchart illustrating the technology for preparing nano-sized magnesium-based composite hydrogen storage materials using magnesium vapor. Magnesium vapor and CNTs are introduced into a hydrogen atmosphere to generate MgH2-CNTs composite hydrogen storage materials. This composite material exhibits high-efficiency hydrogenation characteristics, fast kinetics, and low hydrogen absorption / desorption temperatures. Figure 3 and Figure 4 The XRD diffraction pattern of the Mg-xCNTs magnesium-based composite hydrogen storage material shows that the phase composition mainly includes MgH2, Mg, and CNTs. The sharp diffraction peaks of magnesium hydride indicate that magnesium hydride has a high degree of crystallinity, and the structure of CNTs is stable during the hydrogenation process. CNTs are porous materials with a large specific surface area, which is conducive to hydrogen adsorption and occupancy, providing more diffusion channels for hydrogen atoms, increasing the active sites for H adsorption and dissociation, and CNTs help to shorten the hydrogen diffusion distance, providing more diffusion channels for hydrogen. Increasing the specific surface area, the formation energy barrier of hydrides in nanoparticles decreases with the increase of hydrogen atom solid solution, thereby reducing the hydrogen absorption / desorption reaction in magnesium-based hydrogen storage materials.

Claims

1. A method for preparing a magnesium-based composite hydrogen storage material, characterized in that, The magnesium-based composite hydrogen storage material has the chemical formula MgH2- x CNTs, CNTs attached to the surface of MgH2 particles, x=2wt.%~10wt.%; obtained by blowing nano-CNT powder with magnesium vapor and the resulting MgH2 under a hydrogen atmosphere and rapidly cooling. x CNTs composite materials; CNTs with an inner diameter of 3-5 nm, an outer diameter of 8-15 nm, and a length of 0.5-2 μm; including the following steps: Magnesium vapor is generated by heating industrial magnesium blocks in a hydrogen atmosphere; or industrial magnesium vapor is used directly, with the pressure maintained at 3-5 MPa; in the hydrogen atmosphere, the magnesium vapor and hydrogen in the heating chamber fully form nano-sized gaseous MgH2, and the gaseous MgH2 is carried by the hydrogen flow to pass through the partition and blow away the CNTs on the partition. The escaped MgH2 vapor was rapidly cooled at a rate of 20±5℃ / min to recover MgH2- x CNTs composite powder, with a cooling temperature of 20℃±5℃.

2. The method for preparing magnesium-based composite hydrogen storage material according to claim 1, characterized in that, Magnesium vapor is generated by heating industrial magnesium blocks in a hydrogen atmosphere. Specifically, industrial magnesium blocks with a purity of not less than 99.98% are used. First, a vacuum is drawn, and then high-purity hydrogen is introduced under heating conditions at a hydrogen pressure of 3-5 MPa. The temperature is then raised to 900-1200℃ to generate magnesium vapor.

3. The method for preparing magnesium-based composite hydrogen storage material according to claim 1, characterized in that, The industrial magnesium block is processed as follows: the surface oxide film is removed by polishing and grinding in a vacuum environment, the polished magnesium block is placed in a heating chamber, a vacuum is drawn, and then high-purity hydrogen is introduced at a hydrogen pressure of 1-3 MPa, and the process is repeated 2-3 times.

4. The method for preparing magnesium-based composite hydrogen storage material according to claim 1, characterized in that, CNTs have a purity of >95%, with a mass range of 2wt.%-10wt.%, an inner diameter of 3-5nm, an outer diameter of 8-15nm, and a length of 0.5-2μm.

5. The method for preparing magnesium-based composite hydrogen storage material according to claim 1, characterized in that, The partition in the heating chamber used to hold CNTs materials has a one-way channel that allows only Mg / MgH2 vapor and hydrogen to pass through.

6. The method for preparing magnesium-based composite hydrogen storage material according to claim 1, characterized in that, Maintain a temperature of 700-850℃ when collecting magnesium hydride powder.

7. The method for preparing magnesium-based composite hydrogen storage material according to claim 1, characterized in that, Magnesium hydride vapor is condensed using circulating cooling water to form magnesium hydride powder.

8. The application of the magnesium-based composite hydrogen storage material obtained by the preparation method according to any one of claims 1-7 in hydrogen storage devices.

Citation Information

Patent Citations

  • Preparation process for nanometer magnesium-based hydrogen storage alloy hydride

    CN105692553A

  • Magnesium and multi-wall nano carbon tube composite hydrogen storage material and process for preparing same

    CN1699611A